2021
DOI: 10.1016/j.cej.2020.126265
|View full text |Cite
|
Sign up to set email alerts
|

2-Mercaptobenzimidazole derivative of chitosan for silver sorption – Contribution of magnetite incorporation and sonication effects on enhanced metal recovery

Abstract: Synthesis of magnetic and non-magnetic mercaptobenzimidazole chitosan derivatives.• Silver sorption is enhanced by sonication in terms of kinetics and thermodynamics.• Selectivity for precious metals vs. base metals, especially in presence of EDTA.• High desorption efficiency and stability of the sorbent at recycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 102 publications
1
25
0
Order By: Relevance
“…Figure 9 plots present the calculated TBARS values of chicken breast fillets which were packaged with the most active film, i.e., the LDPE/CS_BO10 film, as well as with the "blank" LDPE film. The storage period was seven (7) and fourteen (14) days and the storage temperature was 4 • C. The initial TBARS values of chicken breast fillets were estimated at around 0.14 mg MDA/kg. Such values are consistent with others reported previously [31,32].…”
Section: Lipid Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 plots present the calculated TBARS values of chicken breast fillets which were packaged with the most active film, i.e., the LDPE/CS_BO10 film, as well as with the "blank" LDPE film. The storage period was seven (7) and fourteen (14) days and the storage temperature was 4 • C. The initial TBARS values of chicken breast fillets were estimated at around 0.14 mg MDA/kg. Such values are consistent with others reported previously [31,32].…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Although CS cannot be used directly in industrial extrusion molding processes, CS based materials have been recently reported as versatile and cost-competitive materials for various industrial applications [ 4 , 5 , 6 , 7 ]. To overcome the obstacles of this raw material use for such applications, the co-extrusion of the CS with synthetic polymers such as LDPE is proposed by researchers [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…a source of pressure, of power E T ). Then, it is possible to calculate the parameter W S as: (5) US could be used only when Q T = 0 (Figure 3) from t 1 to t 2 . Alogenation of aromatic hydrocarbon 20 6.31 [10] Glucose oligomerization 20 6.67 [11] Furoin alkylation 25 22.7 [12] Condensation between nitrobenzaldehyde and acetone 59 483.9 […”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The preparation of innovative heterogeneous catalysts using US in their synthesis procedure have been proposed, for example, for iron based catalysts for Fischer-Tropsch process [4]. US have been also applied to increase the performance of sorptiondesorption processes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Fe 3 O 4 nanoparticles were synthesized by the hydrothermal coprecipitation of ferric and ferrous salts according to the method previously reported by Elwakeel et al [68], derived from Massart [69]. The two precursors (i.e., FeSO 4 ⋅7H 2 O, 5.0 g, and (NH 4 )Fe(SO 4 ) 2 ⋅12H 2 O, 17.35 g) were dissolved in demineralized water (250 mL).…”
Section: Synthesis Of Sorbents 221 Synthesis Of Fe 3 O 4 Nanoparticlesmentioning
confidence: 99%